The Impact of Fiscal Decentralization on Poverty in Indonesia: A Literature Study - Heru Dian Setiawan; Kumba Digdowiseiso; Nazli Aziz (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
This research aims to analyze the impact of fiscal decentralization on poverty levels in Indonesia. The research method used is literature study analysis by collecting and analyzing ten journals that examine the relationship between fiscal decentralization and poverty. The research results show variations in the impact of fiscal decentralization on poverty. Several studies found a positive relationship, highlighting the positive role of fiscal decentralization in reducing poverty levels, especially in urban areas and the Western Region of Indonesia. However, there are also findings that show a negative or insignificant impact, emphasizing the role of certain indicators in influencing the results. In conclusion, the impact of fiscal decentralization on poverty in Indonesia is contextual, depending on the regional situation and the indicators used. Therefore, it is necessary to carry out more in-depth analysis and careful comparisons to understand the impact of fiscal decentralization comprehensively. Meanwhile, the government needs to consider the results of this research in formulating policies to reduce poverty levels in various regions of Indonesia